Social Security Guide : The White Paper and the Beveridge Report Compared - Great Britain. Office of the Minister of Reconstruction. Social insurance ; Great Britain. Inter-departmental Committee on Social Insurance and Allied Services. Social insurance and allied services ; Beveridge, William Henry Beveridge, Baron, 1879-1963; Clarke, Joan Simeon (London : The Social Security League)
1944-10-01 1944 1940s 20 pages for the children. The only way to solve this is by producing more goods so that the aged can have more without the workers and the children going without. Luckily we are producing more. If we maintain a level of near-full employment, and if we make the best use of new inventions and industrial techniques (as we have been doing in the war), we may be able to increase our output more rapidly than in the past so that we can manage the pensions easily without cutting into the claims of other age groups. The Beveridge pension was based on this idea. He thought that we should start the new pensions at a very low rate, and then work up gradually year by year until the pensions reached full rates in 1965. By then he hoped that our production would be so much increased that we could take the pensions in our stride. The money which he saved this way he allocated to the children. The gradual stepping-up of pensions is practised in New Zealand, where, as in the Beveridge Plan, pensions on a needs basis are granted in the interim to those who need them. The Government White Paper treats pensions otherwise. Pensions will not, on present plans, ever reach the ultimate Beveridge rate of 40/- double and 24/- single, but they will be paid at their maximum from the beginning of the scheme. Whereas the Beveridge pension would have started in 1945 at 25/- double and 14/- single, the Government pensions will start at 35/- double and 20/- single. Many elderly persons who would not have lived to climb up to the future Beveridge rates, will now start on the ampler pension. However, even this proposal is not free from snags. Beveridge calculated the sum needed to provide the basic needs of old persons. Allowing for the 25 per cent. price rise, this works out at 37/- double, including margin, and rent at a lower figure than for other beneficiaries. At 35/-, and assuming no higher rise in prices, the pensioner couple will lack 2/- worth of necessaries weekly if they have no other means. They too will have to go off to assistance. In fact 75 per cent. of all supplementary pensioners to-day are already receiving in total more than the Government's proposed pension. This is the problem. The old are permanent beneficiaries, not temporary. The sick will probably recover, the unemployed find work again. But the aged never will again be young. As it is, old age pensions will absorb 25 per cent. of the whole cost of the Government scheme including the new medical service. If all pensioners were to receive 40/- double or 25/- single, whether they needed it or not, there would be a further strain on the social security budget. Either the community would have to set aside more in taxation or contributions, or some other category of social security beneficiaries would have to sacrifice. The Government propose to meet need, but not more than need, by allotting a further 5 per cent. of the Social Security budget to what it calls Assistance Pensions. In total the aged are due to receive 31 per cent. of the whole social security expenditure. 7. DETAILS OF THE SCHEME — This section is not intended to be a complete guide either to the White Paper or to the Beveridge Report, nor to be a substitute 11 15X/2/453/3